The Crime of Blasphemy in Indonesia: A Comparative Study - Abdullah, Abdullah (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Religion Blasphemy has occasionally been committed in numerous media. Blasphemy instances that started out in print media have since proliferated in the virtual world thanks to numerous features and platforms. Because freedom of religion is guaranteed and protected by the Indonesian Constitution, anyone who blasphemes against a particular faith may face severe legal consequences.Purposes of the Research: This study aims at analyzing the offense of blasphemy against religion in the perspective of Islamic law and Indonesian law.Methods of the Research: This type of research is legalistic, doctrinal or normative. The approach used in normative or legalistic research include a concept approach, a statute approach, historical approach, case approach, and comparative approach. However, this study only uses comparative approach since it analyzes of regarding blasphemous crimes in perspective Indonesian and Islamic criminal laws.Results of the Research: The government enacted various laws and rules to maintain religious harmony. However, in terms of law enforcement, are the provisions most frequently used to charge those who commit religious blasphemy. Whereas from the standpoint of Islamic law, blasphemy can take the form of defiling (tadnis), insulting (istihza), ridiculing (syatama), insulting (saba), cursing (taq), and challenging Islamic principles as well as engaging in actions that diverge from Islamic teachings (bid'ah). The Qur'an and the Hadith contain prohibitions against blasphemous acts, but the means of punishment are found in the nomenclature of Ijtihad of the Ulama, which was later incorporated into the laws of many Islamic nations. As a result, the formulation of punishments for blasphemers varies greatly.